Employing women's rights as a racist weapon: The case of Giorgia Meloni in Italy's radical right - Lasio, D.; Girei, E.; Oliveira, J. M. de.; Piras, L.; Serri, F. (Women's Studies International Forum, 2026)
This study analyses how Giorgia Meloni, leader of the Italian radical right party Fratelli d'Italia and current Prime Minister, employs women's rights as a discursive strategy to legitimise nationalist and anti-immigration positions. Drawing on scholarship in gender, postcolonial and migration studies, it reveals how Meloni's standing for (carefully selected) women's rights serves to nurture and perpetuate orientalised representations of Muslim migrants, grounded in the same binary thinking that justifies colonialism and white supremacy. Based on the analysis of Meloni's social media posts published between January 2015 and September 2022, we argue that her representations of women's rights function as discursive weapons deployed to uphold racialised and exclusionary nationalist agendas. By contextualising her defence of women's rights within her broader self-positioning as the “Christian mother of the homeland”, we highlight her dismissal of gender politics, contributing to existing debates on femonationalism.